SORBTION-PHOTOMETRIC DETERMINATION OF ZINC ION FROM THE COMPOSITION OF INDUSTRIAL CAKE OF NON-FERROUS METALLURGICAL ENTERPRISES - Mirzakhmedov Rustamjon Mirkhamidovich; Jumayev Mannon Nafasovich; Imomnazarova Khumorabonu acute kizi; Tursunbayeva will Ababakir daughter (Scholars Digest Publishing, 2023)
To choose dimethylglioxym as an organic reagent for the zinc ion contained in wastewater technological waters and cupcakes at industrial and environmental facilities, to develop an express method of immobilizing the dimethylglioxym reagent to different fiber carriers and obtaining a complex with the zinc metal ion.
Keywords: zinc ion, dimethylglioxime, organic reagent, immobilization, sorbtion-photometric determination.